3D microstructure controls on mineral carbonation. Issue 47 (May 2021) - Herring, Anna; King, Penelope L.; Saadatfar, Mohammad; Mahdini, Fatin; Kemis Yahyah, Afiq Muzhafar; Andò, Edward
Highlights: 3D microstructure and mineralogy investigated in mineral carbonation experiments. Time-resolved measurements show evolution of reaction product density and mineralogy. Carbonation increases amorphous reaction product density. Reaction progress and products are linked to microstructural characteristics. Abstract: Magnesium-based mineral carbonation experiments in model porous columns are presented. The temporal evolution and interplay of 3D microstructure and mineralogy was quantified using a novel combination of X-ray computerized tomography (CT), and mineralogical analyses, conducted at five timepoints over 108 days. We constrain bulk reaction progress (X-ray diffraction, XRD), surface 2D reaction rates (non-destructive diffuse reflectance Fourier transform infrared spectroscopy, DRIFTS) as well as 3D reaction progress (X-ray CT). A new method of normalizing X-ray CT attenuation intensity values was used to provide a proxy measurement for the evolving density of the cement phase to quantify reaction progress on a 3D, microscopic level. The results demonstrate how 3D structural characteristics impact reaction progress; e.g., regions within samples with reduced access to connected void volume exhibit slower reaction, while enhanced access to connected void promotes carbonate formation. Our study shows that 3D characterization is essential for understanding the fundamental processes in mineral carbonation, whereas non-destructive 2D characterization defines reaction rates at the surface−CO2 interface.